Teaching Russian Language in Uzbek Universities (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Monitoring interest in learning the Russian language is one of the main activities to support and promote the Russian language. The relevance of the article is due to the insufficient number of modern studies devoted to the position of the Russian language in the academic educational space. The purpose of the study is to trace the dynamics of studying Russian as a foreign language at Uzbek universities over the past five years and identify the priority factors that led to the choice of Russian for study. The results obtained indicate positive dynamics both at the state level: there is a smooth increase in educational quotas in the departments of Russian language and literature, and at the individual level: student responses demonstrate a positive attitude towards the Russian language and culture.